Pengembangan Buku Ajar Projek Kreatif Dan Kewirausahaan Berbasis Augmented Reality Untuk Meningkatkan Hasil Belajar Siswa Kelas XI Teknik Audio Video Di SMK Negeri 1 Kediri - Ridho Nugroho; Edy Sulistiyo; Rina Harimurti; M. Syariffuddien Zuhrie (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The absence of student textbooks in the new Creative and Entrepreneurial Project subjects in accordance with the current Merdeka Curriculum causes students to be less familiar with Creative and Entrepreneurial Project material. Therefore, researchers developed an Augmented Reality-Based Creative and Entrepreneurial Project Teaching Book. The research conducted is a type of research and development (research and development). The product development model uses the ADDIE model which consists of Analyze, Design, Development, Implementation, and Evaluation. The development of textbooks uses augmented reality as a supporting media in textbooks. This research design adapts the One Group Pretest Posttest Design, with data collection techniques using questionnaires, observations, and tests. The research subjects involved 28 students of class XI Audio Video Engineering 2 at SMK Negeri 1 Kediri and validators consisting of two lecturers in the Electrical Engineering Education Study Program, and one teacher teaching Creative Projects and Entrepreneurship subjects at SMK Negeri 1 Kediri. The results showed that the level of validity of the textbook in terms of expert assessment was 91% with very valid criteria. The level of practicality of the book in terms of students' responses was 93% with very practical criteria. Learning outcomes with multiple choice tests showed an average pretest score of 64.64, while the average posttest score was 88.04. Based on the Wilcoxon test which shows the difference or increase in pretest and posttest scores has a significance value of 0.000. The significance value of the calculated results thus falls in the H0 rejection area because the significance value of 0.00 <0.05, in other words that the pretest and posttest scores have a significant difference or increase. Based on the calculation and analysis of student learning outcomes data, it can be concluded that the Augmented Reality-Based Creative and Entrepreneurial Project Teaching Book developed is effective in improving student learning outcomes.